Motivational Drive in Non-copulating and Socially Monogamous Mammals - Portillo, Wendy; Paredes, Raúl G. (Frontiers in Behavioral Neuroscience, 2019)
Motivational drives guide behaviors in animals of different species including humans. Some of these motivations, like looking for food and water, are crucial for the survival of the individual and hence for the preservation of the species. But there is at least another motivation that is also important for the survival of the species but not for the survival of the individual. Undoubtedly, sexual motivation is important for individuals to find a mate and reproduce, thus ensuring the survival of the species. In species with sexual reproduction, when males find a female in the appropriate hormonal conditions, they will display sexual behavior. However, some healthy males do not mate when they have access to a sexually receptive female, even though they are repeatedly tested. These non-copulating individuals have been reported in murine, cricetid and ungulates. In humans this sexual orientation is denominated asexuality. Asexual individuals are physically and emotionally healthy men and women without desire for sexual intercourse. Different species have developed a variety of strategies to find a mate and reproduce. Most species of mammals are polygamous; they mate with one or several partners at the same time, as occur in rats, or they can reproduce with different conspecifics throughout their life span. There are also monogamous species that only mate with one partner. One of the most studied socially monogamous species is the Prairie vole. In this species mating or cohabitation for long periods induces the formation of a long-lasting pair bond. Both, males and females share the nest, show a preference for their sexual partner, display aggression to other males and females and display parental behavior towards their pups. This broad spectrum of reproductive strategies demonstrates the biological variability of sexual motivation and points out the importance of understanding the neurobiological bases of sexual motivational drives in different species.